The Invisible College of International Lawyers in Private International Law Today - Hess , Burkhard; Requejo Isidro, Marta (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
These pages elaborate briefly on Oscar Schachter’s celebrated reflections about an invisible college of international lawyers, with a focus on today’s private international law.